Upside : profiting from the profound demographic shifts ahead - Gronbach, Kenneth W.; Moye, M. J. (AMACOM, American Management Association, 2017)
Demographics not only define who we are, where we live, and how our numbers change, but-for those who can read beyond the raw figures-they open up hidden business opportunities that lie ahead. Upside puts this powerful yet little-understood science to work finding answers. Demographer Kenneth Gronbach synthesizes reams of data to show how generations impact markets and economies, and how to target promising trends.